GROWTH PATTERNS OF TERM SMALL-FOR-GESTATIONAL-AGE BABIES - Johari, Muhammad Afiq; Synn, Hong Soo (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Catch-up growth is important in bringing a child back to pre-retardation growth. Term small-for-gestational-age (SGA) children with a lack of catch-up growth are at risk of short stature, growth retardation and impaired cognitive function. Early recognition of those who failed to achieve catch-up growth is important as they could benefit from early follow-up and nutritional assessment and if indicated, growth hormone therapy. This study aimed to determine the proportion of term SGA infants born in University Kebangsaan Malaysia Medical Centre (UKMMC) who achieved catch-up growth with respect to height velocity, and the associated factors for catch-up growth. METHODOLOGY This retrospective longitudinal cohort study was conducted in UKMMC. The sample consisted of term SGA children delivered in UKMMC from January 2016 to March 2017. Their anthropometric data were assessed at birth, three months, six months, nine months, one year, 1.5 years, two years and five years. RESULTS A total of 128 term SGA children were included. Catch-up growth was seen as early as three months. By two years of age, 88.3% achieved catch-up growth. Despite good catch-up growth, the rates of wasting and severe wasting in terms of BMI were high from 1.5 years onward, indicating that weights were not proportionate to attained heights. Apart from mixed feeding, we found no other factors related to catch-up growth that was associated with higher catch-up rate. CONCLUSION While more than 85% of the term SGA children eventually achieved catch-up growth by 2 years, the rate of wasting was high. Early identification and early referral are important in these children to optimise outcomes.